Mode I fracture characterisation of rigid and flexible bonded joints using an advanced Wedge-Driven Test. (September 2020) - Manterola, J.; Renart, J.; Zurbitu, J.; Turon, A.; Urresti, I.
Highlights: A new simplified data reduction method based of the Wedge-Driven Test is proposed. GIC values obtained from the DCB test and the WDT+ are in very close agreement. The WDT+ is fully-objective and avoids crack length measurement or COF estimation. The range of test velocities at which quasi-static conditions are met is increased. The WDT+ is suitable for any type of adhesive and bondline thickness configuration. Abstract: The resistance to fracture of a bonded joint is usually evaluated through the experimental characterisation of its fracture toughness. Different test procedures and data reduction methods are available in the literature, such as the ISO-25217 test standard. The need for crack length measurement has led to inaccurate results when large adhesive thicknesses or flexible adhesives were studied. Advanced test protocols based on the insertion of a wedge, such as the Wedge Test (WT) in ASTM D3762 or the Wedge-Driven Test (WDT), simplify the test procedure, but most such procedures do not allow for the measurement of fracture toughness. Further, experimental results are scarce in the literature, especially when dealing with bonded joints and considerable thicknesses. In the present work, an advanced data reduction method based on the WDT is presented: The Wedge-Driven Test Plus (WDT+). The fracture toughness of specimens made by bonding two aluminium adherends with a rigid and a flexible adhesive was measured, and the effect of wedge thickness and test speed at low displacement rates on the test results was analysed. The results were compared with static tests performed in a double cantilever beam (DCB) following ISO-25217. It has been demonstrated that the proposed data reduction method is less sensitive to test speed and enables different adhesive types, and bondline thickness and wedge thickness configurations, thereby improving the WDT available in the literature.